66‐3: A High Reliability PEDOT:PSS/Graphene Transparent Electrode for Liquid Crystal Displays. Issue 1 (May 2017) - Hu, Tao; Wang, Haijun; Shao, Yuan; Zhang, Xia; Liu, Gang; Li, Minghui; Chen, Hsiaohsien; Lee, Yungjui
Abstract : A liquid crystal displays cell (LCD) was assembled by a high reliability PEDOT:PSS/Graphene thin film as its transparent electrode, and the electro‐optical properties of this LCD cell were comparable to the ITO competitor.